The problem is

(2x+1/3)-(x-5/4)=1/2

The problem is

(2x+1/3)-(x-5/4)=1/2

Tutors, please sign in to answer this question.

(2x+1/3)-(x-5/4)=1/2

It looks like there is a confusion about the parenthesis.

Start by distributing the negative sign ("remove" the negative)

2x + 1/3 - x + 5/4 = 1/2

Combine like terms, the x's.

x + 1/3 + 5/4 = 1/2

Get rid of the fractions. It easier for me to think in whole numbers so I multiply everything by the numbers in the denominators (2, 3 and 4). In this case just 3 and 4 are enough since 2 is a factor of 4.

Multiply all terms by 12. 12 is 3 x 4

12x + 4 + 15 = 6

Combine the whole numbers

12x + 19 = 6

Subtract 19 from both sides.

12x = -13

Divide both sides by 12

x = -13/12

Change the answer to a mixed number

x = -1 1/12

*Daisy, you have to use parentheses to avoid double reading!!!!*

(2x + 1)/3 – (x + 5)/4 = 1/2

LCD(2, 3, 4) = 12

. (2x + 1) • 6 (x + 5) • 3 1 • 4

. ——————— – —————— = ———

. 2 • 6 4 • 3 3 • 4

. 12x + 6 – 3x – 15 4

. —————————— = ——

. 12 12

9x – 9 = 4

9x = 4 + 9

9x = 13

. 13 ** 4 **

* x *= ———

. 9

## Comments

Thank you, thats the answer i got one time too but that is not one of the answers so i still dont know what im doing wrong, i get different answers every time